2014
DOI: 10.1016/j.bcp.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of glycolysis in cancers and therapeutic opportunities

Abstract: Upregulated glycolysis, both in normoxic and hypoxic environments, is a nearly universal trait of cancer cells. The enormous difference in glucose metabolism offers a target for therapeutic intervention with a potentially low toxicity profile. The past decade has seen a steep rise in the development and clinical assessment of small molecules that target glycolysis. The enzymes in glycolysis have a highly heterogenous nature that allows for the different bioenergetic, biosynthetic, and signaling demands needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 162 publications
0
37
0
Order By: Relevance
“…Studies with cells that underwent chemically induced partial or total depletion of mitochondrial function have supported a role for mitochondrial dysfunction in cancer drug resistance. It has been reported that partial or total depletion of mitochondrial function causes cancer cells to become less sensitive to the chemotherapeutic drugs cisplatin and paclitaxel …”
Section: Discussionmentioning
confidence: 99%
“…Studies with cells that underwent chemically induced partial or total depletion of mitochondrial function have supported a role for mitochondrial dysfunction in cancer drug resistance. It has been reported that partial or total depletion of mitochondrial function causes cancer cells to become less sensitive to the chemotherapeutic drugs cisplatin and paclitaxel …”
Section: Discussionmentioning
confidence: 99%
“…This unique metabolic behavior of tumor cells is known as the “Warburg effect” (811). In addition to previously reported metabolic states such as the Warburg effect, it is thought that cancer cells may respond differently metabolically to microenvironmental perturbations (1214). We hypothesized that, after exposure to radiation, detectable and quantifiable changes in metabolism might occur, very quickly, from the physical effects of the radiation itself.…”
Section: Introductionmentioning
confidence: 95%
“…have suggested that cancer cells have a heterogeneous metabolic profile and some cancer cell populations use glycolysis as a main energetic pathway, while others use oxidative phosphorylation. The large heterogeneity in mitochondrial glycolytic enzymes, spliced forms, and posttranslational modifications offer an array of antiglycolytic agents as candidate therapeutics on the basis of the molecular signatures of the patient . Several in vivo imaging strategies are now available to assess changes in flux through glycolysis by using positron emission tomography or advanced technologies exploiting the properties of heavy labeled, hyperpolarized nutrients (e.g., choline, acetate, and glutamine) .…”
Section: Summary and Future Research Directionsmentioning
confidence: 99%